Laser Effects on the Prevention and Treatment of Dentinal Hypersensitivity: A Systematic Review - Rezazadeh, Fahimeh (J Lasers Med Sci, 2019)
Introduction: Dentinal hypersensitivity (DH) is an acute intensive tooth pain which can lead to dental annoyances during eating and drinking. Stimulating exposed dentinal tubules by either kind of thermal, tactile, chemical and/or osmotic stimuli is believed to be the cause of this pain. It is hypothesized that dentinal tubules’ orifice occlusion (DOO) can help relieve such dental irritations. Thus, this systematic review was conducted to evaluate the effectiveness of laser application as a prevention and treatment modality on DH reduction. Methods: Electronic databases (MEDLINE, SCOPUS) were searched among randomized clinical trials from January 2007 to December 2016. The extraction of data and quality assessments were carried out by different independent observers. Results: A total of 499 items were found of which3 9 relevant articles were extracted. The profound findings proved lasers’ effectiveness as a treatment of DH. Although some of the researches reported no significant difference between laser and other desensitizing agents, most of the studies suggested that better results (both rapid and long-lasting) were obtained in combined modalities. Furthermore, the preventive role of this new technology has been emphasized as well. Nd-YAG (neodymium-doped yttrium aluminum garnet) and diode lasers reduce DH after bleaching. Lasers can also protect cervical restorations from DH due to tubular occlusion. Moreover, it is suggested to apply lasers in relief of DH following scaling and root planning. Nevertheless, a few researchers dispute its beneficence as a result of placebo effect. Conclusion: The results obtained from several studies in the present review revealed that the application of lasers is effective not only in terms of treatment of DH, but also in the prevention of this intensive tooth pain. Among various types of lasers, the application of Nd:YAG laser has shown the best results in DH treatment.